Contribuições da fonética no processo ensino aprendizagem da pronúncia de línguas no canto - Rocha, Jeanne Maria Gomes da (2013)
This dissertation focuses on the contributions of Phonetics in the teaching and learning processes of languages pronunciation in Singing. For that, it investigates a teaching proposal based on this discipline of Linguistics, the Phonetics, with emphasis on articulation and representation of speech sounds - the Articulatory Phonetics and the International Phonetic Alphabet (IPA) in practice, the phonetic transcription. It is based on the literature on Phonetics and Phonology, in the Linguistics area, on the Teaching of Languages, in the Applied Linguistics, and on the Diction for Singers, in the Arts - specifically, the field of Music, singing. Based on the diagnosis made on the subject of Diction in technical and undergraduate courses of Singing in institutions in the triangle region of Minas Gerais, it reflects and suggests changes on didactic and pedagogical aspects, related to the training of singers and singing teachers. It intends to contribute with theoretical reflections, teaching materials and methodological approaches for the teaching of pronunciation of the major languages in the classical repertoire performed in Brazil.